Evaluasi E-Peken Sebagai Inovasi Pelayanan Publik Bidang Ekonomi Dalam Memberdayakan Pelaku Usaha Mikro Kecil Menengah di Kota Surabaya - Ananda Dwi Firdaus; Annisa Ika Putri; Sindy Mahrani; Rachmad Dwi Prasetyo; Rayhan Vira Puspita; Rosyidatuzzahro Anisyukurillah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The development of technology and information is very popular among entrepreneurs. In developing MSMEs in Surabaya City, the Surabaya City Government created the E-Peken Application Innovation. But on the other hand, this application still requires improvement and development in terms of the performance of functions and application features so that the application performance runs better and can create a sense of comfort in use by MSMEs players. Not only in terms of applications, the Surabaya City government also needs to evaluate the policy of encouraging ASN and OPD to shop at the E-Peken Application. This study aims to analyze and examine the evaluation of E-Peken as an economic public service innovation in raising the potential of Micro, Small and Medium Enterprises in Surabaya City. The research approach uses a qualitative descriptive method. Data were collected through interviews with informants selected by purposive sampling, field observations, and documentation. The results of this study are 1) Effectiveness, in this case in this case the existence of E-Peken can change and move the motivation of MSMEs actors to join the E-Peken platform 2) Efficiency, in this case the implementation of E-peken has been optimal in providing services despite the lack of socialisation at the beginning of making E-Peken 3) Adequacy, in this case the application of the E-Peken application has been good in achieving goals with the creation of E-Peken. 4) Evenness, this E-Peken platform has been socialized to the people of Surabaya City and can reach the target group.5) Responsiveness, in this case the practice of E-Peken users is very satisfied with the existence of E-Peken because it can reach various groups 6) Accuracy, in this case E-Peken has succeeded in being able to improve public services. Although sometimes it is not optimal because there are sellers who are not MSMEs players but enter their merchandise catalogs into the E-Peken application. In general, it can be concluded that the existence of the E-Peken platform is very helpful for MSMEs players to market their products and make their turnover increase.